Pharmacological and interventional treatment of phantom pain - Vadym V. Biloshytsky; Maryna V. Biloshytska (Ukrainian Neurosurgical Journal)
Phantom limb pain (PLP) is a common and debilitating form of neuropathic pain that occurs after limb amputation significantly impairing patients' quality of life. The aim of this review is to summarize and analyze current data on pharmacological and interventional treatments for PLP, focusing on practical aspects of therapy to improve patients' quality of life and optimize treatment strategies for this complex condition. A review of recent studies and clinical guidelines on PLP management was conducted, including pharmacological approaches (antidepressants, anticonvulsants, gabapentinoids, opioids, and NMDA receptor antagonists) and interventional methods (nerve blocks, radiofrequency procedures, neuromodulation). Pharmacological treatment of PLP has shown variable outcomes. Gabapentinoids, anticonvulsants, and serotonin-norepinephrine reuptake inhibitors have demonstrated moderate efficacy in reducing pain intensity. Opioids may be used only in severe cases due to the risk of dependency and side effects. Interventional methods such as peripheral nerve blocks, radiofrequency ablation, and neuromodulation techniques (spinal cord stimulation, transcranial magnetic stimulation) provide long-term pain relief in refractory PLP cases with minimal side effects. A personalized approach combining pharmacological and interventional methods appears to be the most effective in managing PLP. Further randomized controlled trials are needed to optimize therapeutic strategies. Given the increasing number of amputees due to military actions in Ukraine, the standardization of PLP treatment has become a priority for the medical community.